Chinese Economy in Relation to the World Shipping Industry - Beškovnik, Bojan (Promet - Traffic&Transportation, 2005)
This article presents the influence of the Chinese economyon the World shipping industry. Changes in international economyand shipping market have pushed shipping industry tochange the market strategy. The Chinese trade growth has cometo a point at which any change of the Chinese demand will havean immediate influence on the shipping market (container, drybulk and tanker). Because of the rising demand of the transportof manufactured goods, cooperation between carriers will befurther developed, in order to satisfy the customer's requirements.In addition, shipping companies must change to globallogistic providers.